(3eHGOF h efGgL aj JNUjU GdehGQOs - (3eMeO UZjQ(B, (3LGQjs ((3GdLRGFQ(B:s [(3O(B.(3f(B.],s, 2010)
(3GdGbJUGO GdYehej h Gge GdehGVjY GdNGUI Hg , OQGSI cd ef GdfXQjI GdYVhjI GdfXQjI GdeGOjI GdfXQjI GdYGdejI ddOhdI h fXQjI JNWjW hhXGFa GdOhdI , GdGSS GdadSajI h GdehVhYjI aj eYjGQ (Bpareto (3, fXQjI GdJhGab GdYGe aj JMOjO ejRGfjI GdOhdI h GdfTGW GdYehej h eDKQGJg aj GdJhGRf h QTGOI GdNjGQGJ GdcdjI ddGbJUGO GdhWfj h GdeHGOF GdGbJUGOjI aj GdNjGQGJ GdYehejI h bjGS LOhi GdeTGQjY GdYehejI h efgLjI GdJMdjd GdGbJUGOj ddeTGQjY GdJfehjI GdcHjQI h CNjQG GdJLGQI GdNGQLjI aj GdGbJUGO GdYehejs
Keywords: (3GbJUGO(B- (3GdbWGY GdYGes; (3GdGbJUGO GdYGes; (3GdeGdjI GdYGeIs